IRF2 Affects LPS- and IFN-γ-Induced Pro-Inflammatory Responses, Cell Viability, Migration and Apoptosis of Macrophages by Regulating IRG1 - Qin RX; Ma XY; Han ZY; Ma SY; Shen ZJ; Lu ZH; Sun Y; Yu WL (Journal of Inflammation Research)
Ru-Xue Qin, Xue-Ying Ma, Zi-Yu Han, Shi-Ya Ma, Zhao-jian Shen, Zhong-Hua Lu, Yun Sun,* Wei-Li Yu* The First Department of Critical Care Medicine, the Second Affiliated Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei-Li Yu; Yun Sun, The First Department of Critical Care Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, 230601, People’s Republic of China, Email ywl7026@mail.ustc.edu.cn; sunyunicu@163.comBackground: Members of the interferon regulatory factor (IRF) family are transcriptional regulators that play vital roles in the inflammatory response of macrophages. IRF1, IRF3, and IRF9 regulate the expression of immune-responsive gene 1 (IRG1) in macrophages. However, the role of IRF2 in the inflammatory response of macrophages remains somewhat contradictory. The regulatory relationship between IRF2 and IRG1 and their role in macrophages remain unclear. This study aimed to explore the role of IRF2 and IRG1 in macrophages.Methods: Overexpression plasmids of IRF2 (IRF2-pcDNA3.1) and silencing siRNA targeting IRF2 and IRG1 (si-IRF2, si-IRG1) were constructed and transfected into RAW264.7 cells respectively. Subsequently, cells were treated with LPS and IFN-γ for 24 h. The expression of IRF2, IRG1, iNOS, IL-6, and BCL-xl was detected using Western blotting and qRT-PCR. Cell viability, migration and apoptosis were determined by CCK-8, transwell and flow cytometry. The IRG1 promoter region was cloned into the pGL3-basic plasmid. A dual-luciferase reporter assay was performed to verify the regulatory relationship between IRF2 and IRG1.Results: IRF2 overexpression inhibited the expression of IL-6 and iNOS, cell migration, and apoptosis and elevated the expression of BCL-xl, IRG1, and cell viability of LPS- and IFN-γ-induced macrophages. IRF2 silencing had an opposite effect. IRF2 activated the promoter activity of IRG1. The inhibitory effects on LPS- and IFN-γ-induced proinflammatory responses, cell migration, apoptosis, and enhancing effects on the cell viability of over-expressed IRF2 were reversed by IRG1 silencing.Conclusion: IRF2 promoted the promoter activity of IRG1 and regulated directly the expression of IRG1. IRF2 inhibited LPS and IFN-γ-induced pro-inflammatory responses, cell migration and apoptosis, enhanced cell viability in macrophages through regulating IRG1. IRF2 affected LPS- and IFN-γ-induced pro-inflammatory responses, cell viability, migration and apoptosis of macrophages by regulating IRG1.Keywords: IRF2, IRG1, macrophages, pro-inflammatory responses, apoptosis